(untitled) (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2025)
This article explores the essential roles of fluency and accuracy in speaking, especially in the context of second language acquisition. Fluency refers to the ability to speak smoothly, spontaneously, and with minimal hesitation, while accuracy focuses on the correct use of grammar, vocabulary, and pronunciation. Both aspects are fundamental to communicative competence and play a critical role in language performance. Although fluency and accuracy are often perceived as opposing goals, research shows that they are interdependent and must be developed in tandem for successful oral communication. The article discusses theoretical perspectives, including Krashen’s Input Hypothesis and Swain’s Output Hypothesis, to explain how learners acquire speaking skills over time. It also addresses pedagogical implications, emphasizing the importance of balancing fluency-oriented and accuracy-oriented activities in language instruction. Moreover, the paper highlights the influence of learner needs, context, motivation, and teaching methods on the development of speaking proficiency. Insights from communicative language teaching (CLT) and task- based learning (TBL) are used to demonstrate how fluency and accuracy can be effectively integrated into classroom practices. The article concludes that a flexible, learner-centered approach is key to fostering balanced and confident speakers